2015
DOI: 10.1103/physreve.92.012720
|View full text |Cite
|
Sign up to set email alerts
|

Environment-induced anisotropy and sensitivity of the radical pair mechanism in the avian compass

Abstract: Several experiments over the years have shown that the earth's magnetic field is essential for orientation in birds' migration. The most promising explanation for this orientation is the photo-stimulated radical pair (RP) mechanism. In order to define a reference frame for the orientation task radicals must have an intrinsic anisotropy. We show that this kind of anisotropy and consequently the entanglement in the model are not necessary for the proper functioning of the compass. Classically correlated initial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…There have been several theoretical treatments of spin relaxation in the context of magnetoreception, almost all of which have dealt with generic relaxation mechanisms furnished with phenomenological rate constants [36][37][38][39][40][41]. Intriguingly, a few of these studies have indicated that the compass sensitivity could be enhanced by the inclusion of certain abstract spin relaxation pathways [37,38,40,42,43]. In the following, we discuss the spin relaxation that arises from realistic spin interactions modulated by realistic protein dynamics.…”
Section: mentioning
confidence: 99%
“…There have been several theoretical treatments of spin relaxation in the context of magnetoreception, almost all of which have dealt with generic relaxation mechanisms furnished with phenomenological rate constants [36][37][38][39][40][41]. Intriguingly, a few of these studies have indicated that the compass sensitivity could be enhanced by the inclusion of certain abstract spin relaxation pathways [37,38,40,42,43]. In the following, we discuss the spin relaxation that arises from realistic spin interactions modulated by realistic protein dynamics.…”
Section: mentioning
confidence: 99%
“…There have been several theoretical treatments of spin relaxation in the context of magnetoreception, almost all of which have dealt with generic relaxation mechanisms furnished with phenomenological rate constants [36][37][38][39][40][41]. Intriguingly, a few of these studies have indicated that the compass sensitivity could be enhanced by the inclusion of certain abstract spin relaxation pathways [37,38,40,42,43]. In the following, we discuss the spin relaxation that arises from realistic spin interactions modulated by realistic protein dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this proposal, the photochemistry of isolated cryptochromes in vitro has been found to respond to applied magnetic fields in a manner that is quantitatively consistent with the radical pair mechanism (15). Aspects of the radical pair hypothesis have also been explored in a number of theoretical studies, the majority of which have concentrated on the magnitude of the anisotropic magnetic field effect (9,10,16,17,(19)(20)(21)(22)(23)(24)(25)(26)(27). Very little attention has been devoted to the matter we address here: the precision of the compass bearing available from a radical pair sensor (28).…”
mentioning
confidence: 99%
“…A crucial element in all such calculations is the presence of nuclear spins whose hyperfine interactions are the source of the magnetic anisotropy (8,16). Most studies have focused on idealized spin systems comprising the two electron spins, one on each radical, augmented by one or two nuclear spins (9,(21)(22)(23)(24)(25)(26)(27)34). Only a handful has attempted to deal with realistic, multinuclear radical pairs (10,16,17,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation